The Relationship among Tyrosine Decarboxylase and Agmatine Deiminase Pathways in Enterococcus faecalis - Perez, Marta; Ladero, Victor; del Rio, Beatriz; Redruello, Begoña; de Jong, Anne; Kuipers, Oscar; Kok, Jan; Martin, M. Cruz; Fernandez, Maria; Alvarez, Miguel A. (Frontiers in Microbiology, 2017)
Enterococci are considered mainly responsible for the undesirable accumulation of the biogenic amines (BA) tyramine and putrescine in cheeses. The biosynthesis of tyramine and putrescine has been described as a species trait in Enterococcus faecalis. Tyramine is formed by the decarboxylation of the amino acid tyrosine, by the tyrosine decarboxylase (TDC) route encoded in the tdc cluster. Putrescine is formed from agmatine by the agmatine deiminase (AGDI) pathway encoded in the agdi cluster. These biosynthesis routes have been independently studied, tyrosine and agmatine transcriptionally regulate the tdc and agdi clusters. The objective of the present work is to study the possible co-regulation among TDC and AGDI pathways in E. faecalis. In the presence of agmatine, a positive correlation between putrescine biosynthesis and the tyrosine concentration was found. Transcriptome studies showed that tyrosine induces the transcription of putrescine biosynthesis genes and up-regulates pathways involved in cell growth. The tyrosine modulation over AGDI route was not observed in the mutant Δtdc strain. Fluorescence analyses using gfp as reporter protein revealed PaguB (the promoter of agdi catabolic genes) was induced by tyrosine in the wild-type but not in the mutant strain, confirming that tdc cluster was involved in the tyrosine induction of putrescine biosynthesis. This study also suggests that AguR (the transcriptional regulator of agdi) was implicated in interaction among the two clusters.